Antimicrobial and cytotoxic properties of calcium-enriched mixture cement, Iranian propolis, and propolis with herbal extracts in primary dental pulp stem cells - Mohammad Esmaeilzadeh; Shirin Moradkhani; Fahimeh Daneshyar; Mohammad Reza Arabestani; Sara Soleimani Asl; Soudeh Tayebi; Maryam Farhadian (Restorative Dentistry & Endodontics, 2023)
ObjectivesIn this study, natural substances were introduced as primary dental pulp caps for use in pulp therapy, and the antimicrobial and cytotoxic properties of these substances were investigated.Materials and MethodsIn this in vitro study, the antimicrobial properties of calcium-enriched mixture (CEM) cement, propolis, and propolis individually combined with the extracts of several medicinal plants were investigated against Enterococcus faecalis, Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. Then, the cytotoxicity of each substance or mixture against pulp stem cells extracted from 30 primary healthy teeth was evaluated at 4 concentrations. Data were gathered via observation, and optical density values were obtained using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) test and recorded. SPSS software version 23 was used to analyze the data. Data were evaluated using 2-way analysis of variance and the Tukey test.ResultsRegarding antimicrobial properties, thyme alone and thyme + propolis had the lowest minimum inhibitory concentrations (MICs) against the growth of S. aureus, E. coli, and P. aeruginosa bacteria. For E. faecalis, thyme + propolis had the lowest MIC, followed by thyme alone. At 24 and 72 hours, thyme + propolis, CEM cement, and propolis had the greatest bioviability in the primary dental pulp stem cells, and lavender + propolis had the lowest bioviability.ConclusionsOf the studied materials, thyme + propolis showed the best results in the measures of practical performance as a dental pulp cap.